2012
DOI: 10.2106/jbjs.k.00340
|View full text |Cite
|
Sign up to set email alerts
|

A Study in Vivo of the Effects of a Static Compressive Load on the Proximal Tibial Physis in Rabbits

Abstract: Compressed rabbit physes generate biochemical changes in collagens, proteoglycan, and cellular and tissue matrix architecture. Changes potentially weaken overall physeal strength, consistent with the Hueter-Volkmann principle, and lend understanding of the causes of pathological conditions of the physis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The powder was transferred to a sterile tube containing 3 to 5 mL of TRI Reagent (Molecular Research Center, Cincinnati, Ohio), and total RNA was isolated according to the manufacturer's protocol. The total RNA was purified with a PerfectPure RNA Tissue Kit (5 PRIME, Gaithersburg, Maryland) 12 . Purified RNA was shipped on dry ice to the Biomedical Genomics…”
Section: Methodsmentioning
confidence: 99%
“…The powder was transferred to a sterile tube containing 3 to 5 mL of TRI Reagent (Molecular Research Center, Cincinnati, Ohio), and total RNA was isolated according to the manufacturer's protocol. The total RNA was purified with a PerfectPure RNA Tissue Kit (5 PRIME, Gaithersburg, Maryland) 12 . Purified RNA was shipped on dry ice to the Biomedical Genomics…”
Section: Methodsmentioning
confidence: 99%
“…Individual harvested specimens were divided in half with one portion placed in 10% neutralbuffered formalin for histological analysis and the other in RNAlater for reverse transcription-quantitative PCR to determine human-and murine-specific gene expression related to sample remodeling. Specimens placed in RNAlater were ground to powders under liquid nitrogen and purified total RNA was obtained by previous methods (11). Total RNA was reverse-transcribed and qPCR was completed after 40 cycles of the standard protocol on an Applied Biosystems 7500 instrument (Life Technologies, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Sample quantities were normalized to ribosomal protein (P0) and plots of fold change compared 20-to 10-week gene expression data. Gene data were statistically analyzed by a student t-test with errors given as standard errors of mean values and p50.05 was considered significant (11).…”
Section: Methodsmentioning
confidence: 99%
“…Our study found that as stimulation increased in compression days, chondrocytes tended to hypertrophy that showed gene expression of Col-10 and MMP-13 increased obviously, Col-2 was degradation and the structural integrity of chondrocytes was damaged. Although these four genes (Agg, Col-2, Col-10 and MMP-13) demonstrated changes critical for physeal structural integrity and function, it is likely that the broader effects of static compression on rabbit physes would have been forthcoming if additional genes and the counterpart secreted molecules had been assessed 15) . Studies of cell mechanics found that the mechanical properties of chondrocytes could significantly affect the physiological function of the articular cartilage.…”
Section: Differences In Viscoelastic Properties Of Chondrocytes On DImentioning
confidence: 99%